Application of biochar derived from rice straw for the removal of Th(IV) from aqueous solution. Issue 10 (3rd July 2018) - Dong, Lijia; Chang, Kaikai; Wang, Linxia; Linghu, Wensheng; Zhao, Donglin; Asiri, Abdullah M.; Alamry, Khalid A.; Alsaedi, Ahmed; Hayat, Tasawar; Li, Xue; Wu, Xilin
ABSTRACT: Biochar is increasingly used as a low-cost and effective adsorbent for heavy metals in wastewater. Herein, biochar pyrolyzed from rice straw was employed as an adsorbent for the removal of Th(IV) from aqueous solutions. The sorption of Th(IV) on biochar was strongly dependent on pH, but independent on ionic strength at pH < 6.4. The inner-sphere complexation dominated the sorption mechanism of Th(IV) on biochar. The competition for Th(IV) between aqueous or surface-adsorbed cations/anions and functional groups of biochar was pivotal for Th(IV) sorption. The thermodynamic data suggested that Th(IV) sorption was a spontaneous and endothermic process.